A high-sensitivity biaxial resonant accelerometer with two-stage microleverage mechanisms. (11th December 2015) - Ding, Hong; Zhao, Jiuxuan; Ju, Bing-Feng; Xie, Jin
Abstract: This paper presents a design and experimental evaluation of a micro-electro-mechanical system biaxial resonant accelerometer with two-stage microleverage mechanisms. The device incorporates two pairs of double-ended tuning fork resonators coupled to a single proof mass. The two-stage microleverage mechanisms possess a higher amplification factor than single-stage microleverage mechanisms, so that the proposed accelerometer has a high level of sensitivity. In addition, a low level of cross-axis sensitivity is realized because of the decoupling beams. The accelerometer is theoretically analyzed and then simulated in the system level by the finite element method. The device is fabricated in a silicon-on-insulator wafer. The experimental results demonstrate that the average differential sensitivity of the resonant accelerometer is 275 Hz g −1 at a resonant frequency of 290 kHz under a polarization voltage of 5 V. The measured cross-axis sensitivity is lower than 3.4%.